Identification of gene networks jointly associated with depressive symptoms and cardiovascular health metrics using whole blood transcriptome in the Young Finns Study - Mishra, Binisha H.; Raitoharju, Emma; Mononen, Nina; Saarinen, Aino; Viikari, Jorma; Juonala, Markus; Hutri-Kähönen, Nina; Kähönen, Mika; Raitakari, Olli T.; Lehtimäki, Terho; Mishra, Pashupati P. (Frontiers in Psychiatry, 2024)
Background: Studies have shown that cardiovascular health (CVH) and depression are related. We aimed at identifying gene networks jointly associated with depressive symptoms and cardiovascular health metrics using whole blood transcriptome.We analyzed human blood transcriptomic data to identify gene coexpression networks, termed as gene modules, shared by Beck's depression inventory (BDI-II) score and cardiovascular health (CVH) metrics as markers of depression and cardiovascular health respectively. BDI-II scores were derived from Beck's depression inventory, a 21-item self-report inventory that measures characteristics and symptoms of depression. CVH metrics were defined according to the American Heart Association's criteria using seven indices based on smoking, diet, physical activity, body mass index (BMI), blood pressure, total cholesterol, and fasting glucose. Joint association of the modules, identified with weighted co-expression analysis, as well as the member genes of the modules with the markers of depression and CVH was tested with multivariate analysis of variance (MANOVA). Results: We identified a gene module with 256 genes significantly correlated with both BDI-II score and CVH metrics. Based on MANOVA test results adjusted for age and sex, the module was jointly associated with both depression and CVH markers. The three most significant member genes from the module were YOD1, RBX1, and LEPR. Genes in the module were enriched with biological pathways involved in brain diseases such as Alzheimer's, Parkinson's and Huntington's disease. Conclusions: The identified gene module and its member genes can provide new joint biomarkers for depression and CVH.